A nők ellen vagy a nők ellen is? Iuvenalis 6. szatírájának bevezetőjéről - Gellérfi, Gergő (Antikvitás & Reneszánsz, 2018)
The opening of Juvenal’s longest and maybe the most well-known poem, Satire 6, is based on the ancient concept of the “Ages of Man”, starting from the reign of Saturn and ending with the flight of the two sisters, Pudicitia and Astraea. The first part of this 24-line-long passage depicts the Golden Age making use of two different sources: the idealized Golden Age appearing in Vergil’s poetry among others and the prehistoric primitive world from the Book 5 of Lucretius. The Juvenalian Golden Age, presented briefly in a naturalistic way, is a curious amalgam of these two traditions, being the only time in human history according to the poet when marital fidelity was unblemished. However, while reading Satire 6, it seems far from obvious that the lack of adultery should be attributed to higher morals. Albeit Juvenal presents a great variety of women’s sins in Satire 6, the poem’s central motif is infidelity beyond doubt, which is called the most ancient of all sins by the poet, being the only one that appeared in the Silver Age already. This is his cause for looking back to the mythological past in the introductory lines of the “Women’s Satire”; but as his words reveal it, the return to this state of the world and humanity seems neither possible nor desirable to him...